The self in the process of coping with change - Amiot, Catherine E (University of Ottawa (Canada), 2004)
On the basis of theoretical work on the self, coping, and self-determination, the goal of this thesis was to understand the role of both structural and more flexible self-related variables in the process of adapting to change as well as the consequences of this adaptation process. It was hypothesized that, in a changing situation, a structural aspect of the self, namely, the sense of self, would predict more positive appraisals and less negative appraisals toward this change. Appraisals and coping, in turn, were hypothesized to represent adaptation processes mediating the associations between sense of self and various consequences. The consequences investigated included psychological well-being, as well as changes in some more flexible aspects of the self, such as in the importance attributed to a new self-component and in self-determined motivation. Three studies were conducted to test these hypotheses. Study 1 (N = 35) was a preliminary laboratory experiment designed to induce change (experimental condition) vs. no change (control condition). The impact of the change manipulation on the associations between sense of self and appraisals was first tested using hierarchical moderated regression analyses. While a stronger negative association was found between sense of self and negative appraisals in the experimental (i.e., change) than in the control condition, sense of self did not predict positive appraisals, both in the experimental and in the control conditions. Through mediational analyses, negative appraisals were found to significantly mediate the sense of self - well-being association. Study 2 (N = 80) aimed at further testing these hypotheses by including another mediator in the sense of self - well-being association, namely, coping strategies. Again, a stronger association was observed between sense of self and negative appraisals in the experimental than in the control condition. Furthermore, mediational analyses confirmed the mediating role of (1) negative appraisals in the sense of self -disengagement-oriented coping association, (2) task-oriented coping in the positive appraisals-well-being relationship, and (3) disengagement-oriented coping in the negative appraisals-well-being association. Using a three-wave longitudinal design, Study 3 (N = 311) aimed at testing the entire hypothesized model among university students as they were experiencing the transition to university. Using structural equation modeling involving true intraindividual change analyses, sense of self was found to predict both positive and negative appraisals toward the transition to university. While positive appraisals positively predicted task-oriented coping strategies used to deal with the transition and negatively predicted disengagement-oriented coping, negative appraisals positively predicted both forms of coping. Finally, task-oriented coping positively predicted psychological well-being as well as increases in both identification as a university student and in academic motivation, whereas disengagement-oriented coping predicted less well-being and a decrease in academic self-determination. Through tests of indirect effects, the mediating role of appraisals and coping was confirmed. Implications of the findings and future research avenues are further discussed.
Keywords: Education, Educational Psychology.; Psychology, Clinical.